CD248 enhances tissue factor procoagulant function, promoting arterial and venous thrombosis in mouse models. (7th May 2021) - Kapopara, Piyushkumar R.; Safikhan, Nooshin S.; Huang, Jenny L.; Meixner, Scott C.; Gonzalez, Kevin; Loghmani, Houra; Ruf, Wolfram; Mast, Alan E.; Lei, Victor; Pryzdial, Edward L.G.; Conway, Edward M.
Abstract: Background: CD248 is a pro‐inflammatory, transmembrane glycoprotein expressed by vascular smooth muscle cells (VSMC), monocytes/macrophages, and other cells of mesenchymal origin. Its distribution and properties are reminiscent of those of the initiator of coagulation, tissue factor (TF). Objective: We examined whether CD248 also participates in thrombosis. Methods: We evaluated the role of CD248 in coagulation using mouse models of vascular injury, and by assessing its functional interaction with the TF‐factor VIIa (FVIIa)‐factor X (FX) complex. Results: The time to ferric chloride‐induced occlusion of the carotid artery in CD248 knockout (KO) mice was significantly longer than in wild‐type (WT) mice. In an inferior vena cava (IVC) stenosis model of thrombosis, lack of CD248 conferred relative resistance to thrombus formation compared to WT mice. Levels of circulating cells and coagulation factors, prothrombin time, activated partial thromboplastin time, and tail bleeding times were similar in both groups. Proximity ligation assays revealed that TF and CD248 are <40 nm apart, suggesting a potential functional relationship. Expression of CD248 by murine and human VSMCs, and by a monocytic cell line, significantly augmented TF‐FVIIa‐mediated activation of FX, which was not due to differential expression or encryption of TF, altered exposure of phosphatidylserine or differences in tissue factor pathway inhibitor expression. Rather, conformation‐specific antibodies showed that CD248 induces allosteric changes in the TF‐FVIIa‐FX complex that facilitates FX activation by TF‐FVIIa. Conclusion: CD248 is a newly uncovered protein partner and potential therapeutic target in the TF‐FVIIa‐FX macromolecular complex that modulates coagulation.